Current Topics in Salmonella and Salmonellosis 2017
DOI: 10.5772/67438
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Risks and Antibiotic Resistance of Salmonella in Poultry Production Chain

Abstract: Salmonella spp. are bacteria that cause salmonellosis, a common form of foodborne illness with major impact on human health and huge inancial losses in poultry industry. The incidence of notiied cases of salmonellosis has declined from a peak of 24 per 100,000 in 2009 to 20.4 reported cases per 100,000 population in 2013, with S. enteritidis and S. typhimurium being the most commonly reported serovar in EU. Salmonella spp. has been detected in a range of foods, and outbreaks have predominantly been associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 54 publications
1
48
0
Order By: Relevance
“…Commonly found in bird feces [104], L. monocytogenes high incidence in carcasses is likely to arise from cross-contamination during processing. At the end of the process, cooling of meat is intended to inhibit the multiplication of pathogens, but it was observed that in chilled poultry meats, the prevalence of L. monocytogenes was still quite relevant, confirming that refrigeration is not enough to inhibit the proliferation of this cold-resistant pathogen.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Commonly found in bird feces [104], L. monocytogenes high incidence in carcasses is likely to arise from cross-contamination during processing. At the end of the process, cooling of meat is intended to inhibit the multiplication of pathogens, but it was observed that in chilled poultry meats, the prevalence of L. monocytogenes was still quite relevant, confirming that refrigeration is not enough to inhibit the proliferation of this cold-resistant pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the establishment of strict biosecurity measures at farm level (including Salmonella -free poultry feed and water), vaccination programs in the parent flocks, and testing/removal of positive flocks from production have been used as control measures [104]. Additionally, the use of feed additives and acidified food and water have been encouraged, as the pH reduction is expected to have a protective effect on the feed, milling and feeding equipment and on the general environment [104].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations